(untitled) (Research, Society and Development, 2021)
Objective: To analyze the structure of social representations of users of health services about neglected diseases. Methodology: qualitative study based on the Theory of Social Representations, in its structural approach, composed of an intentional and non-probabilistic sample of 126 users of health services. Data collected by questionnaire of free evocations to the term inducer neglected diseases and analyzed by the technique of the quadrant of four houses, aided by the software Ensemble of Programs Permettant l’analyse DES Evocations 2005 and by the similarity analysis. Results: They evidenced a representational structure of users of health services on neglected diseases, constituted by three dimensions: individual, social and imagery, which were managed by a central nucleus formed by the neglect and ignorance cognemas. The dimensions and central core of this representational structure presented knowledge socially elaborated by the participants and their meanings about the prevention, control and treatment of these diseases. Conclusion: The representational structure implied the construction of collaborative practices by users of health services to develop strategies to cope with neglected diseases.